ESTIMA Journal: 15 Years of History and New Advances (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
For 15 years ago ESTIMA Journal began with the purpose, at that time, to become the o cial communication vehicle of Brazilian Stomatherapy Association (SOBEST) and to edit/publish topics relevant to the education or improvement of SOBEST members and health professionals involved with Stomatherapy (...)